Quality Control of Fried Pepper Oils Based on GC-MS Fingerprints and Chemometrics - Jianlong Li; Yu Zhang; Qiang Cui; Zhiqing Zhang; Xiaoyan Hou (Foods)
Zanthoxylum bungeanum Maxim. (huajiao) and Zanthoxylum armatum DC. (tengjiao), also known as Sichuan pepper, is a popular spice owing to its unique aroma and taste. Fried pepper oils are liquid condiments with unique flavors extracted from the pericarps of huajiao and tengjiao. To investigate the volatile profiles of the two different fried pepper oils, solid-phase microextraction (SPME) coupled with gas chromatography–mass spectrometry (GC-MS) was employed. The results revealed that D-limonene, linalyl acetate, linalool, myrcene, and ocimene significantly contributed to the overall flavor of huajiao oils. In addition, linalool, D-limonene, sabinene, myrcene, and linalyl acetate were identified as the main odorants in tengjiao oils. Finally, a characteristic chromatogram for the volatile compounds of each oil was established through the Similarity Evaluation System for the Chromatographic Fingerprint of Traditional Chinese Medicine, and the similarity thresholds of huajiao oils and tengjiao oils were 0.984 and 0.998, respectively. Linalool, sabinene, and linalyl acetate were markers for distinguishing between ZAOV samples and ZAOC samples. And germacrene D, linalool, sabinene, linalyl acetate, and β-myrcene were markers for distinguishing ZBOV samples from ZBOC samples.